Analysis of the Relationship Between Concept Mastery and Problem-Solving Skills of Pre-Service Biology Teachers in Human Physiology Courses - Finga Fitri Amanda*; Sutiman Bambang Sumitro; Sri Rahayu Lestari*; Ibrohim Ibrohim (Jurnal Pendidikan Sains Indonesia, 2021)
21st century learning focuses on problem-solving skills. A higher level of education requires an understanding of a more systematic concept to elaborate problems. Problem-solving skill is one of the fundamental cognitive processes. It involves higher order thinking to discover solutions or ideas. This research aims to analyze the relationship between concept mastery and problem-solving skill of pre-service biology teacher in human physiology courses. This is descriptive correlational research conducted in Sulthan Thaha Saifuddin State Islamic University Jambi. The sample was selected using the purposive sampling technique. Respondents in this study were 33 students in semester VI. The instrument used in the study was an essay test of concept mastery integrated with problem-solving. The results showed that the average scores of the students' concept mastery and problem-solving were 56.8 and 58.0, respectively. Both included in the poor category. It also showed that there was a relationship between students' concept mastery and problem-solving skill. The correlation value was 0.76, with a significance value of p0.05; therefore, it included in the strong category.